2003
DOI: 10.1046/j.1540-8175.2003.03014.x
|View full text |Cite
|
Sign up to set email alerts
|

Imagent Improves Endocardial Border Delineation, Inter‐reader Agreement, and the Accuracy of Segmental Wall Motion Assessment

Abstract: Use of Imagent during echocardiographic imaging improves EBD, providing a significant improvement in inter-reader agreement in SWM evaluation with echo and greater than a threefold improvement in SWM scoring accuracy with MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Gender and interethnic differences in intimal thickening, as demonstrated histologically on autopsy material, indicated a strong genetic control on this process. Nanda et al [116] studied racial differences in thoracic aorta thickness among IS patients and found that black populations have a lower prevalence of extracranial atherosclerotic disease than Caucasians and this difference cannot be explained by the existing risk factors alone.…”
Section: Genetic Predisposition Affects Both Coronary and Carotid Athmentioning
confidence: 99%
“…Gender and interethnic differences in intimal thickening, as demonstrated histologically on autopsy material, indicated a strong genetic control on this process. Nanda et al [116] studied racial differences in thoracic aorta thickness among IS patients and found that black populations have a lower prevalence of extracranial atherosclerotic disease than Caucasians and this difference cannot be explained by the existing risk factors alone.…”
Section: Genetic Predisposition Affects Both Coronary and Carotid Athmentioning
confidence: 99%
“…The use of intravenous contrast agents has been shown to improve the assessment of segmental wall motion and interobserver agreement by enhancing the endocardial border delineation (22,23). Because RTCE permits the analysis of both wall motion and perfusion, the injection of contrast agents during RTCE should also assist in detecting WMA.…”
Section: Feasibility Of Mpi Image Interpretationmentioning
confidence: 99%
“…A shell encapsulating the gas bubble is essential for the longevity. Proposed shell materials include protein (Albunex Ò [8] and Optison [9]), lipid (SonoVue Ò [10], Definity TM [11] and Imagent Ò [12]) or surfactants (ST68 [13]) and the gas can be perfluorocarbon [9][10][11][12][13], sulfur hexafluoride [10,13], air [14,15] or some other inert gas or gas mixture.…”
Section: Introductionmentioning
confidence: 99%